Guiding at-risk youth through learning to work : lessons from across Europe - (:unkn) unknown (Publications Office of the European Union, 2010)
This Cedefop report presents the findings of a study carried out in 2009 on guidance policies and practices in Europe that support young people at risk. Specifically, the report examines guidance measures (formal, informal and non-formal guidance) that aim to support school completion, those which aid reintegration of disengaged young people, and measures to ease the transition of the young from school to work. The study takes account of both mainstream provision and specific projects which fall within the definition of guidance adopted by the Council of the European Union (Resolution of the Council ..., 2004). The study suggests that coordinated approaches should be combined with outreach work to identify and reach those individuals who are in most urgent need of support. The partnership between different actors needs to be based on mutual trust and respect but also needs to place the interests of the young people first. Guidance professionals and teaching staff providing guidance services should learn how to establish a good working relationship with at-risk youth. Further, parental involvement, together with competent teachers, guidance practitioners, youth and social workers, labour-market actors, and healthcare providers, are considered essential support in the young person's transition. (BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; P 1.7 Benachteiligte; P 1.1 Jugendliche; I 2.2 Europa; Berufsberatung; Bildungsberatung; Bildungsbegleitung; Benachteiligter Jugendlicher; Europäische Union